Flow Injection Amperometric Method with Dialysis Sample Pretreatment for Determination of Ascorbic Acid - Pipoon Bunpeng (2018)
A flow injection amperometric method with dialysis sample pretreatment for determination of ascorbic acid (vitamin C) has been developed. Standard/sample solution (50 μL) was injected into a donor stream (deionized water) via an injection valve. The sample zone was passed through a dialysis unit to separate the analyte from the matrices. The dialysate containing ascorbic acid, in the acceptor stream of 0.1 M phosphate buffer pH 5.6, was flowed to the amperometric detector for current measurement. Ascorbic acid was electrochemically oxidized at glassy carbon electrode giving an anodic peak current proportional to ascorbic acid concentration. A linear calibration graph in range of 50-800 mg/L ascorbic acid was obtained. The relative standard deviation of 10 replicate injections was 1.5 % for 50 mg/L of ascorbic acid. A sample throughput of 20 h-1 was achieved. The proposed method was applied to vitamin C tablets and fruit juice samples collected from drug stores, supermarkets and local suppliers in Chiang Mai. The results obtained for vitamin C samples are agreed well with the labeled values, and comparable with those determined by voltammetric method. The proposed method is rapid, low reagent consumption and does not suffer from colored and colloidal substances presented in the sample.